Role of LOX-1 (Lectin-Like Oxidized Low-Density Lipoprotein Receptor 1) as a Cardiovascular Risk Predictor: Mechanistic Insight and Potential Clinical Use. Issue 1 (January 2021) - Barreto, Joaquim; Karathanasis, Sotirios K.; Remaley, Alan; Sposito, Andrei C.
Abstract : Atherosclerosis, the underlying cause of cardiovascular disease (CVD), is a worldwide cause of morbidity and mortality. Reducing ApoB-containing lipoproteins—chiefly, LDL (low-density lipoprotein)—has been the main strategy for reducing CVD risk. Although supported by large randomized clinical trials, the persistence of residual cardiovascular risk after effective LDL reduction has sparked an intense search for other novel CVD biomarkers and therapeutic targets. Recently, Lox-1 (lectin-type oxidized LDL receptor 1), an innate immune scavenger receptor, has emerged as a promising target for early diagnosis and cardiovascular risk prediction and is also being considered as a treatment target. Lox-1 was first described as a 50 kDa transmembrane protein in endothelial cells responsible for oxLDL (oxidized LDL) recognition, triggering downstream pathways that intensify atherosclerosis via endothelial dysfunction, oxLDL uptake, and apoptosis. Lox-1 is also expressed in platelets, where it enhances platelet activation, adhesion to endothelial cells, and ADP-mediated aggregation, thereby favoring thrombus formation. Lox-1 was also identified in cardiomyocytes, where it was implicated in the development of cardiac fibrosis and myocyte apoptosis, the main determinants of cardiac recovery following an ischemic insult. Together, these findings have revealed that Lox-1 is implicated in all the main steps of atherosclerosis and has encouraged the development of immunoassays for measurement of sLox-1 (serum levels of soluble Lox-1) to be used as a potential CVD biomarker. Finally, the recent development of synthetic Lox-1 inhibitors and neutralizing antibodies with promising results in animal models has made Lox-1 a target for drug development. In this review, we discuss the main findings regarding the role of Lox-1 in the development, diagnosis, and therapeutic strategies for CVD prevention and treatment.